By His Excellency, Thomas Chittenden, Esquire ... A proclamation : ... I do hereby appoint Wednesday the twenty-sixth day of April next, to be observed as a day of public fasting, humiliation and prayer ... Given under my hand at Arlington, this thirty-first day of March, in the year of our Lord, one thousand seven hundred and eighty-six . (1786)
March 31, 1786 Proclamation by Governor Thomas Chittenden setting April 26th as a day of public fasting, humiliation and prayer in the state.